The Concept of Leader and Leadership in the Proto-Studies of Leadership. The European Tradition (UNWE Yearbook, 2021)
The study aims to make a review of the main concepts regarding leadership (especially political leadership) in the period prior to the emergence of the contemporary theories of leadership. The author reveals one of the problematic issues in the above field – this is the full ignoring or neglect of the concepts, theories and studies before the XIX century as a main or significant base of the leadership studies. Nowadays there is only one explanatory concept for the period before the XIX century and this is "The great man theory" (or Heroic theory) which the author sees as highly insufficient and as a flaw in the overall evolution of the leadership theory. This is a flaw that at some point should be rectified.